Relationships between dental fluorosis and fluoride concentrations in bottled water and groundwater in low-income children in Mexico - Irigoyen-Camacho, Maria Esther; Perez-Perez, Nora; Zepeda-Zepeda, Marco Antonio; Velazquez-Alva, Maria Consuelo; Castaño-Seiquer, Antonio; Barbero-Navarro, Ignacio; Sanchez-Perez, Leonor (Frontiers in Oral Health, 2023)
Introduction The aim of the current study was to investigate associations between dental fluorosis in children living in low socioeconomic areas in Mexico, and fluoride concentrations in tap water, fluoride concentrations and in bottled water, and body mass index (BMI). Methods A cross-sectional study involving 585 schoolchildren aged 8–12 years was conducted in communities in a southern state of Mexico with >0.7 parts per million (ppm) fluoride in the groundwater. The Thylstrup and Fejerskov index (TFI) was used to evaluate dental fluorosis, and the World Health Organization growth standards were used to calculate age-adjusted and sex-adjusted BMI Z-scores. A BMI Z-score ≤ −1 SD was used as the cut-off point for thinness, and multiple logistic regression models for dental fluorosis (TFI ≥ 4) were constructed. Results The mean fluoride concentration in tap water was 1.39 ppm (SD 0.66), and the mean fluoride concentration in bottled water was 0.32 ppm (SD 0.23). Eighty-four children (14.39%) had a BMI Z-score ≤ −1 SD. More than half (56.1%) of the children presented with dental fluorosis in TFI categories ≥ 4. Children living in areas with higher fluoride concentrations in the tap water [odds ratio (OR) 1.57, p = 0.002] and bottled water (OR 3.03, p < .001) were more likely to have dental fluorosis in the severe categories (TFI ≥ 4). BMI Z-score was associated with the probability of dental fluorosis (TFI ≥ 4; OR 2.11, p < 0.001), and the effect size was 29.3%. Discussion A low BMI Z-score was associated with a higher prevalence of dental fluorosis in the severe category. Awareness of the fluoride concentrations in bottled water may help prevent dental fluorosis, particularly in children exposed to several high fluoride content sources. Children with a low BMI may be more vulnerable to dental fluorosis.